P. Oxy. LX X VII 5123 and the economic relations between the Apion estate and its coloni adscripticii - Benaissa, A (University of Warsaw, 2021)
Starting from a detailed interpretation of P. Oxy. LXXVII 5123 (ad 555), I argue that the Apion estate favoured a tenancy arrangement with its enapographoi georgoi, the farmers registered on its tax-rolls. Such leases left them with a marketable surplus of the produce in remuneration, which they could sell either to their own estate or to outside parties. Contrary to the now current view of Apionic enapographoi georgoi as directly managed permanent employees or wage labourers, the evidence reviewed suggests that they were not an economically distinct and homogenous labour group.